A Neighborhood-Level Analysis of Low-Income Housing Tax Credit Developments in the State of California and Los Angeles County - Victoria Basolo; Edith Huarita; Jongho Won (Urban Science, 2022)
Some housing researchers have criticized the United States housing subsidy scheme referred to as the Low-Income Housing Tax Credit (LIHTC) program for failing to promote better opportunities for low-income persons. In this study, therefore, we examine the socio-economic and built-environment characteristics of LIHTC developments at the neighborhood level. Specifically, we aim to investigate the characteristics associated with LIHTC developments compared to neighborhoods without this kind of development. We focus on California statewide initially and then narrow our focus to examine LIHTC developments in Los Angeles County (LAC). We then compare the results from the two levels of government. We compiled data from several sources including the U.S. Census Bureau, the State of California, the Southern California Association of Governments, and other secondary sources; used Geographic Information Systems (GIS) to aid in creating several location-based indicators; and employed logistic regression for analyses. Our results show that LIHTC developments at the statewide and county levels tend to be in racially/ethnically diverse neighborhoods with higher levels of economic hardship, lower rents, a higher percentage of renters, and spatial clustering of LIHTC developments. With LAC removed from the state-level analysis, economic hardship is not more likely to occur in LIHTC neighborhoods. This finding suggests, except for in LAC, state policies may be having some level of success in locating LIHTC housing outside of hardship areas. Finally, in examining additional built-environment variables in LAC, we find LIHTC developments were more likely to be in a neighborhood with a park than other neighborhoods in the county. We discuss these results further and conclude with a brief recap of results, policy recommendations, and suggestions for future research.